Hsa_circ_0000652 Aggravates Inflammation by Activation of Macrophages and Enhancement of OX40/OX40L Interaction in Ankylosing Spondylitis - Song, Minkai; Gao, Jiawen; Yan, Tao; Bi, Enguang; An, Taixue; Wang, Xiangyu; Jiang, Weizhou; Wang, Ting; Chen, Zishuo; Shi, Zhanjun; Zhang, Chao; Xiao, Jun (Frontiers in Cell and Developmental Biology, 2021)
Circular RNAs (circRNAs) have emerged as important roles in various inflammatory processes of rheumatic diseases. However, their expression profiles and influences in pathogenesis of ankylosing spondylitis (AS) remain unclear. Here, we revealed the differential expression profiles of circRNAs in peripheral blood mononuclear cells (PBMCs) in AS by circRNA sequencing. We screened the differentially expressed circRNAs in AS and verified that hsa_circ_0000652 was up-regulated and had potentials to be a biomarker of progression. Functionally, hsa_circ_0000652 promoted proliferation and cytokines production in macrophages and inhibited apoptosis. Through dual luciferase assays and RNA pull down assays, we demonstrated that hsa_circ_0000652 acted as a competing endogenous RNA (ceRNA) by binding with hsa-miR-1179 and regulate OX40L, which is characterized as a co-stimulatory molecule and found to be up-regulated in AS patients. As a result, hsa_circ_0000652 aggravates the inflammation in co-culture system containing CD4+ T cells and macrophages via OX40/OX40L interaction. Our findings suggest that hsa_circ_0000652 is up-regulated in AS patients and may serve as a pro-inflammatory factor in macrophages and a positive regulator of OX40/OX40L by sponging hsa-miR-1179.